The Effects of Hand Muscle Stretching Program on Reducing Hand Spasticity among Stroke Patients at Home in Trang Province - Tiparat, Wararat; Wauters, Yanat (Princess of Naradhiwas University Journal, 2020)
This quasi-experimental research of one group pretest-posttest aimed to compare hand spasticity before and after using a hand stretching program that based on Rood’s Theory, the prolonged stretch technique. Sample was 27 stroke patients who were in rehabilitation phase at home in central Trang province which the stroke patients had participated in the hand stretching program for 9 weeks. The program was validated by a panel of experts (3 persons). Data were collected using a test of knowledge about hand stretching, and a measurement test of the spasticity (MAS). The reliability of the knowledge test was verified using the KR-20, yielding a value of 0.75. The reliability of the measurement test of hand spasticity was verified using Cronbach’s alpha coefficient, yielding a value of 0.82. Data were analyzed by frequency, percentage, paired t-test, and Wilcoxon sign rank test. The research found that 1) after participating the hand stretching program, the caregivers had a mean score of knowledge about stretching the hand muscles significantly higher than before participating the program and 2) after participating the hand stretching program, the stroke patients had a mean score of hand spasticity higher than before participating the program, with a statistical significance at the level of 0.05. According to the findings, it is suggested that health personnel should implement this innovation, the hand stretching program using PVC pipe, to reduce hand spasticity of stroke patients in the rehabilitation phase at home. The result of the treatment program was satisfied in terms of faster recovery of hand spasticity condition, and it could also help patients to be able to take care of themselves at home after recovery.